Environmental effects on the dynamic characteristics of the Gulburnu Highway Bridge - Bayraktar, Alemdar; Altunisik, Ahmet Can; Sevim, Baris; Ozsahin, Talat Sukru (TAYLOR & FRANCIS LTD, 2014)
This paper investigates environmental effects on dynamic characteristics of isolated highway bridges constructed with the balanced cantilever method using ambient vibration test. The Gulburnu Highway Bridge located on the Giresun-Espiye state highway is selected as an application. Measurement time, frequency span and effective mode number are selected by considering similar studies found in the literature. The first measurement tests are conducted in June 2009 and traffic over the bridge is used as a source of ambient vibrations to obtain the dynamic characteristics such as natural frequencies, mode shapes and damping ratios. The second measurement tests are conducted in November 2011 using ambient vibrations and the dynamic characteristics are obtained, experimentally. The output-only modal identification of the bridge is effectively carried out using the enhanced frequency domain decomposition method in the frequency domain and stochastic subspace identification method in the time domain. At the end of the study, experimentally identified dynamic characteristics are compared with each other and environmental effects are investigated in detail. The analysis results reveal that the identified natural frequencies provide an effective indication for changes of dynamic characteristics of the bridge due to environmental effects. Significant variability in the identified natural frequencies is changing by up to maximum 14%.
Keywords: operational modal analysis; dynamic characteristics; environmental effect; enhanced frequency domain decomposition method; stochastic subspace identification method; highway bridge; ambient vibration test; MEASURED MODAL FREQUENCIES; IDENTIFICATION; VARIABILITY; VIBRATION; FOOTBRIDGE; MODEL; Engineering